Games and playing: a literature review on children learning english as a second language - MESCOUTO, Adriely Mayara Pinheiro (2023)
This paper makes a theoretical reflection about children's English as a second language learning through games and playing. The central focus is to understand how games and playing can contribute to children’s English language learning based on other research. In this sense, it seeks to establish meaningful relationships between playing and English language learning and teaching, based on thinkers who advocate teaching through playing. The collection of material was done through a narrative review of literature in digital platforms, where 1 final essay (TCC), 3 articles, 3 dissertations and 1 thesis were selected. The selected texts were read, analyzed and summarized aiming at answering the research question of understanding the contribution of the use of games and playing in the English language learning process of children. The results presented here show how effective games and playing are and how they create motivating environments for learning.